2015
DOI: 10.1515/amm-2015-0050
|View full text |Cite
|
Sign up to set email alerts
|

Methodology for the Construction of a Rule-Based Knowledge Base Enabling the Selection of Appropriate Bronze Heat Treatment Parameters Using Rough Sets

Abstract: Decisions regarding appropriate methods for the heat treatment of bronzes affect the final properties obtained in these materials. This study gives an example of the construction of a knowledge base with application of the rough set theory. Using relevant inference mechanisms, knowledge stored in the rule-based database allows the selection of appropriate heat treatment parameters to achieve the required properties of bronze. The paper presents the methodology and the results of exploratory research. It also d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…For this reason, the step of classification could be selected in various ways. Most of the obtained feature vectors were separable linearly, therefore many classification methods could be used to solve problems such as: fuzzy logic [46], clustering method [47], nearest mean, k-nearest neighbour classifier [36,48,49], neural network [50][51][52][53][54][55], naive Bayes classifier [56], classifier based on word coding [36], linear discriminant analysis (LDA) [57,58], support vector machine [59,60], rules based on the theory of rough sets [61], Gaussian mixture models (GMM) [62,63]. The authors decided to analyse LDA, nearest neighbour (NN) classifier, and the nearest mean (NM) classi- Fig.…”
Section: Analysed Classifiersmentioning
confidence: 99%
“…For this reason, the step of classification could be selected in various ways. Most of the obtained feature vectors were separable linearly, therefore many classification methods could be used to solve problems such as: fuzzy logic [46], clustering method [47], nearest mean, k-nearest neighbour classifier [36,48,49], neural network [50][51][52][53][54][55], naive Bayes classifier [56], classifier based on word coding [36], linear discriminant analysis (LDA) [57,58], support vector machine [59,60], rules based on the theory of rough sets [61], Gaussian mixture models (GMM) [62,63]. The authors decided to analyse LDA, nearest neighbour (NN) classifier, and the nearest mean (NM) classi- Fig.…”
Section: Analysed Classifiersmentioning
confidence: 99%
“…The problem of classification was already discussed in literature [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45]. Neural networks were described in many scientific articles [37][38][39][40][41][42].…”
Section: Nearest Neighbour Classifiermentioning
confidence: 99%
“…Accordingly, the object may certainly not belong to the rough set (if it does not belong to any of the approximations), it may certainly belong to a rough set (if it belongs to both approximations), or the situation may occur when, based on the indicated features, we can not rule out the object membership in a rough set (upper approximation). The approach using rough set theory has shown that, applied to the classification of various methods of the heat treatment of bronze alloy [16,17], this technique gives satisfactory results. It should be noted that building a model of inference for new test materials in a situation where we have only a small number of measurements, as well as incomplete knowledge about the phenomena is difficult and highly biased.…”
Section: Rough Set Theorymentioning
confidence: 99%